PENGARUH KECERDASAN VERBAL-LINGUISTIK DAN KECERDASAN VISUO-SPATIAL TERHADAP KREATIFITAS SISWA - Ansori, Miksan (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2016)
The study examines the influence of verbal-linguistic intelliegence and visuo-spatial intelliegence towards students' creativity at Islamic Boarding School SMP Islam Al A’la Nganjuk. This research was a quantitative  method. The researcher conducted 50 respondents and used stratified random sampling technique. To collect the data used test and. to analyze data  used regression analyze.The study revealed the following result. Firstly, verbal-linguistic intelliegence of students at Islamic Boarding School SMP Islam Al A’la Nganjuk affects significantly the students' creativity by 49,6%. Secondly, visuo-spatial intelliegence of students at Islamic Boarding School SMP Islam Al A’la Nganjuk affects significantly students' creativity by 40,7%. Finally, verbal-linguistic intelliegence and visuo-spatial intelliegence affect significantly students' creativity by 58,2%.  Keywords: verbal-linguistic intelliegence, visuo-spatial intelliegence and students' creativity